Ethical - moral values of offcials and servers in the municipal budget control of Nauta – Iquitos - Velásquez-Lozano, Teddy R. (2019)
The purpose of this research is to present a summary of the functional characteristics of the worker of public administration through a tab with 20 items on Likert scale to evaluate trends positive and negative of committing some kind of administrative dysfunction as well as a summary of the Peruvian legal framework, sustaining new ethical guidelines that will promote the transformation of governancein which the Constitution of the Peru of 1993 and law No. 27815 among others were taken as references. The basic objective of the research was to identify, describe and analyze the values and principles that govern the behavior of the public official, and contribute to greater efficiency in the public service in the Nauta-Iquitos-Peru Local Government. Within the framework of the study considered a premise concerning the formation or transformation of the management towards a new institutionality, as well as the conceptualization and identification of the weakened values that are present in the Peruvian laws, are in turn, reflections and conclusions, which became the researcher, and then describes the development of a methodology for the selectionvalidation and identification of the factors associated with the studied ethical values, demonstrating the validity of the general hypothesis using the Chi-square test.